North Indian peasant Goes to market - Swartzberg, Leon (Delhi, 1970)
This work examines the relationship a town in Bihar, India and its market economy with a nearby village and its peasant economy. The emphasis is on the village and the changes which have taken place in its approximately one hundred years of existence through its contact with the town. The historical development of the village and various aspects of economic and other cultural relationships in the village are described to a large extent in terms of the history, interests, and the attitudes of the most important family in the village. The contrast of the economic and social patterns of the village and town is sufficiently large so as to allow them to be conceptualized separately as household ing and marketing. These two patterns form different economies, peasant and market. Finally, the concept of house holding forms the basis of a definition of the peasant.
Keywords: Rural Development-India